Uji Efek Anti Anafilaksis Kutan Aktif Dari Ekstrak Etanol Bunga Kincung (Etlingera elatior (Jack) R. M. Smith) Pada Mencit Putih Jantan - Widya Kardela; Yufri Aldi; Rozi Efendi (Jurnal Farmasi Higea, 2017)
An assay of the active cuteneous antianaphylactic of the ethanolic extract  Etlingera elatior (Jack). R. M. Smith on white male mice could be determined by measurement of the pro long of occurrence time, the decreased in diameter and the color intensity of the blue bump formed by using blue evan’s solutian as indicator which was given intravenously. The ethanolic extract were given in three different doses (100, 300, 900 mg per kg body weight). Allergic reaction was induced by giving egg’s albumin as antigen. Increasing the dose caused pro long of occurrence time increasing dose, decreased in diameter and the color intensity of the blue bump. The result was analyzed by one way ANOVA and Kruskal Wallis. Result indicated the ethanolic extract of Etlingera elatior (Jack) R. M. Smith had significant effect for each dose (P<0.05).